2014
DOI: 10.1093/mnras/stu2094
|View full text |Cite
|
Sign up to set email alerts
|

Radial migration of the Sun in the Milky Way: a statistical study

Abstract: The determination of the birth radius of the Sun is important to understand the evolution and consequent disruption of the Sun's birth cluster in the Galaxy. Motivated by this fact, we study the motion of the Sun in the Milky Way during the last 4.6 Gyr in order to find its birth radius. We carried out orbit integrations backward in time using an analytical model of the Galaxy which includes the contribution of spiral arms and a central bar. We took into account the uncertainty in the parameters of the Milky W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 75 publications
2
34
2
Order By: Relevance
“…But co-rotation in the Galaxy is unfortunately too far out (8.4−12 kpc, e.g., Martínez-Barbosa et al 2015) to check for direction reversals in the data set of Paper I. At such galactocentric distances, individual 26 Al-emission regions are only a few, they are faint, and they are not associated with spiral arms.…”
Section: Model For the 26 Al Kinematicsmentioning
confidence: 98%
“…But co-rotation in the Galaxy is unfortunately too far out (8.4−12 kpc, e.g., Martínez-Barbosa et al 2015) to check for direction reversals in the data set of Paper I. At such galactocentric distances, individual 26 Al-emission regions are only a few, they are faint, and they are not associated with spiral arms.…”
Section: Model For the 26 Al Kinematicsmentioning
confidence: 98%
“…We adopted the same Galactic model as Martínez-Barbosa et al (2015) where the axisymmetric part of the Galaxy is modelled by using the potential of Allen & Santillan (1991), which consists of a bulge, disk, and a dark matter halo. The parameters that describe the axisymmetric component of the Milky Way are listed in Table 9.…”
Section: Radial Velocity Of the Sun's Siblingsmentioning
confidence: 99%
“…The bar and spiral arms are non transient structures that rotate as rigid bodies with different pattern speeds. The Galactic parameters used in the simulations are taken from Martínez-Barbosa et al (2015).…”
Section: Simulations Set Upmentioning
confidence: 99%
“…By using this technique, Martínez-Barbosa et al (2015) found the distribution of possible positions and velocities of the Sun at its birth (P (R b ), P (V b )). Given that for most of the Galactic parameters, (P (R b )) is peaked around 9 kpc, we assume initially for the Sun's birth cluster r cm = 9 kpc.…”
Section: Simulations Set Upmentioning
confidence: 99%
See 1 more Smart Citation